Conservative Surgical Treatment of Bisphosphonate-Related Osteonecrosis of the Jaw with Er, Cr:YSGG Laser and Platelet-Rich Plasma: A Longitudinal Study. (19th August 2018) - Mauceri, Rodolfo; Panzarella, Vera; Maniscalco, Laura; Bedogni, Alberto; Licata, Maria Ester; Albanese, Antonino; Toia, Francesca; Cumbo, Enzo Maria Giuseppe; Mazzola, Giuseppina; Di Fede, Olga; Campisi, Giuseppina
Abstract : Introduction . The management of bisphosphonate-related osteonecrosis of the jaw (BRONJ), with no evidence-based guidelines, remains controversial. We aimed to evaluate the efficiency of a conservative surgical treatment combining Er, Cr:YSGG laser and platelet-rich plasma (PRP) for the treatment of BRONJ in cancer patients. Methods . We performed a longitudinal cohort study. Inclusion criteria were (1) age ≥ 18 years; (2) cancer diagnosis; (3) treatment with NBP because of the underlying cancer. Results . We consecutively recruited ten patients diagnosed with BRONJ in stage I or II. These patients underwent a surgical laser-assisted therapy together with autologous PRP. At the latest follow-up at 12 months, clinical improvement was observed in eight patients. Registration Number is IRCT20180329039159N1. Conclusion . We could successfully manage the BRONJ utilizing this combined protocol to heal the 30% of surgically treated sites and to improve the 50% of patients' lesions clinically. Our findings suggest that a surgical approach combined with Er, Cr:YSGG laser and PRP benefit cancer patients with general health issues.